2004
DOI: 10.1093/hmg/ddh275
|View full text |Cite
|
Sign up to set email alerts
|

Common DNase I polymorphism associated with autoantibody production among systemic lupus erythematosus patients

Abstract: DNase I could be the most important nuclease for the removal of DNA from nuclear antigens at sites of high cell turnover, and thus may also prevent systemic lupus erythematosus (SLE). Sixteen SNPs were identified by direct DNA sequencing, among which six were selected for genotyping in a larger investigation on the basis of linkage disequilibria among SNPs, their frequency, location and haplotype tagging status. Genetic associations of polymorphisms in DNase I with the risk of SLE and the production of common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 16 publications
2
30
0
2
Order By: Relevance
“…Patients who have low amounts of DNases in their blood are not able to adequately control NET formation and thus may have a higher risk to develop severe sequelae than patients with normal amounts of DNases. It would be of interest, therefore, to analyze the DNase gene polymorphism [57], e.g., in patients with blood stream infections (BSI) and chronically high amounts of NETs in blood values, for example in septic patients [58,59] at high risk for organ failure or in patients with autoimmune disease.…”
Section: Nets and The Putative Pathophysiological Role In Immune Disomentioning
confidence: 99%
“…Patients who have low amounts of DNases in their blood are not able to adequately control NET formation and thus may have a higher risk to develop severe sequelae than patients with normal amounts of DNases. It would be of interest, therefore, to analyze the DNase gene polymorphism [57], e.g., in patients with blood stream infections (BSI) and chronically high amounts of NETs in blood values, for example in septic patients [58,59] at high risk for organ failure or in patients with autoimmune disease.…”
Section: Nets and The Putative Pathophysiological Role In Immune Disomentioning
confidence: 99%
“…142 In addition to the absence of the exon 2 mutation, no SLE-associated SNPs of DNase I were found in a Korean population, but rs1053874 ( þ 2373A/G; Gln244Arg) was associated with the production of anti-dsDNA antibody in this population. 143 Although no association between rs1053874 and SLE susceptibility was found in a Chinese population, a haplotype including rs1053874 was associated with SLE. 144 Two SLE genetic studies related to DNase I performed in a Spanish population found that þ 2035C/G, which is in strong linkage disequilibrium with þ 2373A/G, was significantly associated with SLE.…”
mentioning
confidence: 95%
“…Our previous study revealed that one nonsynonymous SNPs in exon 8, +2373A>G (Gln244Arg), was significantly associated with an increased risk of the production of anti-RNP and anti-dsDNA antibodies among SLE patients (Shin et al 2004). The present study provides, for the first time, information about genetic polymorphisms in DNase II and positive associations of those polymorphisms with important lupus phenotype (renal disorder) among SLE patients in the Korean population.…”
Section: Resultsmentioning
confidence: 99%